Percutaneous ultrasound-guided stellate ganglion block for the treatment of arrythmic storm and stage E cardiogenic shock: case report: Stellate ganglion block in the treatment of arrhythmic storm and cardiogenic shock - Galacho, João; Silva, Doroteia; Cortez-Dias, Nuno; Ribeiro, João Miguel (Journal of the Portuguese Society of Anesthesiology, 2023)
Arrhythmic storm is a medical emergency that complicates severe structural heart disease and is associated with an increased mortality rate. Antiarrhythmic drugs and catheter ablation are the most commonly used therapies. Alternatively, percutaneous ultrasound-guided stellate ganglion blockade is a promising technique for the control of arrhythmic storm in the event of refractoriness or failure of other approaches. We report a case of therapeutic success of left stellate ganglion block in the control of arrhythmic storm complicated by stage E cardiogenic shock with dependence on support by venoarterial extracorporeal membrane oxygenation and intra-aortic balloon. The percutaneous sympathetic block with bupivacaine allowed the control of arrhythmic storm and the continuation of definitive intervention with electrophysiological study. We highlight the therapeutic potential of a minimally invasive and low-risk intervention in the treatment of arrhythmic storm.